Rhodium-Catalyzed Allylation Reactions - Thoke, Mahesh Bhagwan; Kang, Qiang (Synthesis, 2019)
Rhodium-catalyzed allylation reactions are well known for their unique selectivity and reactivity due to the high memory effect of Rh as compared to other metals. These reactions involve the substitution of allylic rhodium intermediates with a diverse range of different nucleophiles, leading to C–C and C–heteroatom bond formation. Modern organic chemists are, however, interested in atom-economical protocols under greener pathways and following recent increased understanding of mechanistic aspects of Rh-catalyzed allylation via the hydrofunctionalization of allenes or alkynes, great strides have made in the design and development of new atom-economical protocols. In this article, we review this field from its beginning to current state.1 Introduction2 Rhodium-Catalyzed Allylic Substitution3 Rhodium-Catalyzed Allylation with Allenes4 Rhodium-Catalyzed Allylation with Alkynes5 Rhodium-Catalyzed Allylation with Dienes6 Rhodium-Catalyzed Allylation by ARO of Oxabicyclic Alkenes7 Rhodium-Catalyzed Enantioselective Allylation in Natural Product and Drug Synthesis8 Conclusion
Keywords: rhodium; allylation; substitution; enantioselective; natural product synthesis